Agent Intellect and Divine Illumination in Thomas Aquinas' Summa Theologiae = Abweichender Titel: Intelecto agente e iluminación divina en la Summa Theologiae de Tomás de Aquino - Echavarría Anavitarte, Martín F. (Cauriensia, 2025)
The theory of knowledge of Thomas Aquinas is strongly influenced by the Aristotelian theory of abstraction and the agent intellect. Along with this theory, Thomas Aquinas also assimilates the Augustinian doctrine of divine illumination. In our paper, we show how Aquinas articulates these two theories, that of the agent intellect and that of divine illumination, in his Summa Theologiae. The agent intellect is the internal formal and efficient principle of human knowledge, but God is also the efficient, exemplary and final cause of human knowledge, inasmuch as He creates the human soul with its innate light, moves it to its operation, regulates it with the Eternal Reasons, and is in whom happiness is all about. In Saint Thomas, the affirmation of the metaphysical consistency of the second causes is not to the detriment of the power of the first Cause, but on the contrary. The causation of its own science by the created intellect, second cause, and the causation of it by God, First Cause, are strongly related and require each other.